Prostaglandin receptor EP4 expression by Th17 cells is associated with high disease activity in ankylosing spondylitis - Klasen, Charlotte (Arthritis Res Ther, 2019)
BACKGROUND: Th17 cells are involved in the pathogenesis of ankylosing spondylitis (AS). However, the mechanism underlying enhanced Th17 cell accumulation in AS remains unknown. The prostaglandin E(2) receptor EP2/EP4 signaling pathway plays a critical role in the development of autoimmune Th17 cells. Interestingly, recent genome-wide association studies (GWAS) have identified five risk alleles for AS in PTGER4, the gene encoding for EP4. The aim of this study was to reveal a possible link between EP4 and disease activity in patients with AS. METHODS: Th17 cells from patients with AS were analyzed for the transcriptional expression of prostaglandin receptor genes by quantitative RT-PCR. Th17 cells from patients with rheumatoid arthritis (RA) and from healthy individuals served as controls. EP4 receptor expression in Th17 cells was assessed ex vivo by flow cytometry and by western blot. Functional analysis using EP4-specific agonists was performed to reveal how EP4 regulates Th17 cells. RESULTS: EP4 is significantly overexpressed in Th17 cells from patients with AS compared to Th17 cells from healthy individuals or patients with RA or psoriatic arthritis (PsA). EP4 upregulation is unique to Th17 cells and is not found in other CD4(+) T cell subsets. Specific activation of EP4 drives Th17 cell development and promotes EP4 expression in a positive feedback loop in AS but not in RA or PsA. Mechanistically, EP4 acts via upregulation of the interleukin-23 receptor (IL-23R), by suppressing the RORγt inhibitor FoxO1 and by enhancing STAT3 phosphorylation. Increased EP4 expression levels in Th17 cells from AS patients correlate with high disease activity as defined by a Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score ≥ 4 (r = 0.7591, p = 0.0016). CONCLUSIONS: EP4 is a potential marker of disease activity in patients with AS. Aberrant EP4 expression might contribute to pathogenic Th17 cell accumulation and represent a new target for the treatment of AS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13075-019-1948-1) contains supplementary material, which is available to authorized users.